A new subgenus with three new species of Agrotis from New Guinea (Lepidoptera: Noctuidae) - VINK, Linda; de VOS, Rob; SINNEMA, Siep; SINNEMA-BLOEMEN, Jannie; ZILLI, Alberto (Fragmenta entomologica, 2022)
Following the examination of museum holdings and recently collected material of noctuid moths from New Guinea, the new subgenus Papuagrotis Vink & Zilli subgen. n. of Agrotis Ochsenheimer, 1816 is described. This is found to consist of at least three montane species new to science that are herein described also, namely Agrotis (Papuagrotis) habbemae Vink & Zilli sp. n., A. (P.) bintangus Vink & Zilli sp. n. and A. (P.) minutus Vink & Zilli sp. n. Characters and relationships of the group with respect to other Agrotis s.l. are reviewed and briefly discussed.